The Art of Regenerative Educatorship (Amsterdam University Press, 2025)
A regenerative current is rising all around us. Stories of the need to reconnect, heal and transform are becoming more urgent, challenging a dominant worldview built on competition, economic growth, extractivism, militarisation and personal gain. Our planet’s resources are stretched beyond their limits, causing widespread suffering and injustice for both humans and non-humans. Yet, each of us holds the potential to cultivate life-affirming futures.